Effect of Crop Establishment Methods on the Performance of Boro Rice (Oryza sativa L.) in the Cooler Region under Light Texture Soil Condition (The Agriculturists, 2010)
An experiment was conducted at the Bangladesh Rice Research Institute regional station, Rangpur to investigate the performances of different establishment methods of Boro rice; variety BRRI dhan29 in light texture soil during Boro 2004-05 and 2005-06 seasons. Five crop establishment methods were tested in a randomize complete block design with three replications. The methods were: 1. Conventional transplanting method 2. System of Rice Intensification (SRI) method, 3. Farmers practice, 4. Seedling throwing method and 5. Direct-Wet Seeded Rice(DWSR) using drum seeder method. Grain yield was influenced by different crop establishment methods in both the seasons. The highest mean grain yield was obtained by BRRI recommended conventional transplanting method (6.27 t ha-1) followed by SRI method (5.70 t ha-1). The highest number of panicles m-2 was obtained from wet DSR by drum seeder method (341 m-2). Effectiveness of tiller (92%) was obtained from the SRI method. The largest number of filled grains per panicle (76) was obtained from the SRI method. The highest 1000-grain weight (23.2 g) was obtained by the farmers method. Less sterility was occurred (30 %) from farmers methods. The highest growth duration (175 days) was observed in farmer method. But the highest field duration of BRRI dhan29 (145 days) was observed in wet DSR using dream seeder.